Forensic Facial Approximation: Study of the Nose in Brazilian Subjects - Strapasson, Raíssa Ananda Paim; Costa, Cláudio; Melani, Rodolfo Francisco Haltenhoff (Journal of forensic sciences, 2019)
Forensic facial approximation is an auxiliary method for human identification and allows facial recognition. The midface, that includes the nose, is vital for the recognition of a familiar face. The purpose of this study was to set hard tissue parameters to estimate nasal width, to test the method to estimate nasal width of Brazilians, and to analyze the relationship between nasal profile and facial type. A total of 246 computed tomography scans (183 females and 63 males) of adults were analyzed in Horos. Bone tissue measurements and facial type classification were performed on the skull scan. Nasal profile morphology was accessed through the tool 3D surface rendering. There was a difference around 3 mm from real to predicted nose through the method to estimate nasal width in Brazilians. So, the method may be used in forensic practice. Straight nose was associated with long face type.